Bioviabilitas Ekstrak Gracilaria sp terhadap Stem Sel Mesenkimal sebagai Terapi Adjuvant Periodontitis - Talsha Irzaputri A; Yoifah Rizka; Sarianoferni (Denta: Jurnal Kedokteran Gigi, 2021)
Background: Gracilaria Seaweed extracts are known to have an antibacterial content that can inhibit the growth of Porphyromonas gingivalis bacteria. P.Gingivalis are dominant in chronic periodontitis as a cause of periodontal tissue damage that can be inhibited by using materials that contain antibacterial effect. Terms of materials to be applied in the oral cavity must be biocompatible, through toxicity tests, one with bioviability test. In this study bioviability test performed on media mesenchymal stem cells. Purpose: To determine bioviability Gracilaria seaweed extract against mesenchymal stem cells as adjuvant therapy of periodontitis. Materials and Methods: study design was post test only control group design. Mesenchymal stem cells in 96 wells were divided into a control group of cells (n=6), media controls (n=6), and treatment (n=6). The treatment group was given Gracilaria seaweed extract with a concentration of 2.5%, 5%, 10%, 20% and 40%. Stem cells were incubated 24 hours before and after treatment. Once given MTT, optical density read with an ELISA reader then calculated the percentage of living cells. Toxic material when living cells <50% and not toxic when living cells >50%. Living cell data were analyzed by statistical test Kruskal Wallis and Man Whitney. Result: Viability cell at 2.5% concentration is 68.59%, 5% concentration = 29.67%, 10% concentration = 4.43%, 20% concentration = 2.5% and 40% concentration = 0.96 %. Conclusion: Extract of seaweed Gracilaria proven not toxic at 2.5% concentration and proved toxic at 5%, 10%, 20% and 40% concentration